EU citizenship and (fundamental) rights: Empirical, normative, and conceptual problems - van den Brink, M (Wiley, 2018)
There is a close connection between EU citizenship and rights, both in the law and literature. This article claims that EU lawyers' understanding of EU citizenship and rights suffers from empirical, normative, and conceptual shortcomings. I will point out that there has been insufficient awareness for the boundedness of EU citizenship, the political structure of the EU and the constraints this (realistically) imposes on the ‘meaningfulness’ of EU citizenship. EU citizenship must not be understood as requiring an elaborate set of equal rights for all Union citizens throuzghout the EU, but valued for its ability to allow its status holders to enjoy (almost) full membership in the Member States of which they do not possess nationality.